Course induced dexterity development and cerebellar grey matter growth of dentistry students: a randomised trial - Benedek Siman (Nature Portfolio, 2021)
Abstract This study primarily focuses on the assessment of dentistry students’ improvement of manual skills resulting from their participation in courses. We aimed to prove that systematic manual skills development significantly improves dexterity. We hypothesized that the dexterity training regimen improves manual dexterity demonstrated by the HAM-Man (Hamburg Assessment Test for Medicine-Manual Dexterity) test scores and CGM (cerebellar grey matter) growth. Thirty volunteers were randomly divided into two equal groups (study and control). Firstly, volunteers were examined by the HAM-Man test and baseline MRI scans. Afterwards, a manual skills development course was launched for the “study group”. Secondly, all the manual skills of the students were evaluated longitudinally, by the HAM-Man test. Simultaneously, the follow-up MRI scans were taken to observe morphologic changes in the cerebellum. The Wilcoxon signed-rank test and Student Paired t-test were used for statistical analyses. Value p < 0.05 was considered significant. After the training, significant growth of CGM as well as improvement on manual skill assessment tests, were found in the study group. Training courses are suitable for preparing students with low levels of dexterity for performing demanding tasks. The improvement is demonstrable by a wire bending test and by bilateral CGM enlargement as well.